Trends in response rate and survival in small-cell lung cancer patients between 1997 and 2017. (May 2019) - Lattuca-Truc, Mickaël; Timsit, Jean-François; Levra, Matteo Giaj; Ruckly, Stéphane; Villa, Julie; Dumas, Isabelle; Pinsolle, Julian; Ferrer, Léonie; Guillem, Pascale; Moro-Sibilot, Denis; Toffart, Anne-Claire
Highlights: This study compared response to chemotherapy and survival from 1997 to 2017. The ORR to 1st-line chemotherapy was 74% in 1997–2009 and 71% in 2010–2017. In metastatic patients median survivals were 8.6 months and 8.9 months respectively. It highlights a lack of improvement in response and survival from 1997 to 2017. Ongoing clinical trials are encouraging. Abstract: Introduction: Median survival of small-cell lung cancer (SCLC) patients is usually around 1 year. The advent of new drugs may have slightly improved their prognosis. We aimed to assess whether SCLC response to chemotherapy and survival had changed over time. Methods: Consecutive SCLC patients were included at Grenoble University Hospital, France. We compared the patients' characteristics, response to chemotherapy and survival between 1997–2009 (period 1) and 2010–2017 (period 2). Results: A total of 529 patients were identified, of whom 498 received a first line of chemotherapy and 279 a second line. The majority (n = 290, 58%) had extensive disease. The objective response rate (ORR) to first-line chemotherapy in metastatic patients was 63% in period 1 and 62% in period 2; the ORRs to second-line chemotherapy were 39% and 29%, respectively. Median overall survival from first-line chemotherapy was 13.2 months (interquartile range [IQR] 7.4–24.4) in period 1 and 11.2 months (IQR 7.1–21.2) in period 2. Mortality in these two periods did not differ significantly even after adjustment for prognostic factors (hazard ratio [HR] = 0.82, 95% confidence interval [CI] 0.66–1.00). The factors independently associated with death were cardiovascular comorbidities (HR = 1.28 [95%CI 1.05–1.55]), liver comorbidities (HR = 1.31 [95%CI 1.03–1.65]), poor ECOG performance status (3–4 vs. 0–1, HR = 2.45 [95%CI 1.83–3.30]) and extensive disease (HR = 2.69 [95%CI 2.18–3.33]). Conclusions: Since 1997, there has been no improvement in the survival or response rate to chemotherapy of SCLC patients. There is a desperate need for new approaches in this setting.